HISTOPAT HOLOGY OF Fasciola hepatica INFECTION IN Meriones unguiculatus - Mendes, Eveline Albuquerque (2012)
Three groups of 60 individuals of Meriones unguiculatus were inoculated with 3, 5, and 8 metacercariae each, of Fasciola hepatica. Multifocal areas of hemorrhage, necrosis, and fibrosis were observed in the liver, the kidney and other organs in the peritoneal cavity in 20.6% of the infected animals. Liver was the most damaged organ, indicating hepatotropism during parasite development. At 20 days post inoculation, dilatation of the bile ducts and of the hepatic artery branches, disruption of the hepatic vein and hemorrhage were evident in the periportal areas. At 30 and 40 days, adherent worms and eggs of F. hepatica were recovered from the inner wall of the bile duct and thoracic and abdominal cavities. Histopathological examination revealed track-like lesions varying from acute hemorrhagic necrosis to active granulomas with organized fibrotic areas generated by eggs and worms in the parenchyma of the liver and mesenteric lymph nodes. Most of the chronic lesions showed the presence of lymphocytes and macrophages. In addition, liver, lungs,diaphragm, spleen, mesenteric lymph nodes, kidneys, pancreas, and small intestine also showed some foci of inflammatory infiltrates with mixed polymorphonuclear and mononuclear cells. These results indicate that infection by F. hepatica may be maintained in M. unguiculatus and that the parasites develop in the different organs.